Metabolomics Approach Revealed Polyunsaturated Fatty Acid Disorders as Pathogenesis for Chronic Pancreatitis−Induced Osteoporosis in Mice - Xinlin Liu; Fenglin Hu; Yunshu Zhang; Shurong Ma; Haihua Liu; Dong Shang; Peiyuan Yin (Metabolites)
Background: Osteoporosis is frequently observed in patients with chronic pancreatitis, and both conditions are closely associated with systemic metabolic disorders. However, the underlying mechanisms linking chronic pancreatitis and osteoporosis remain unclear. Methods: In this study, we utilized high−performance liquid chromatography–mass spectrometry (HPLC−MS) to conduct metabolomics and lipidomics analyses on pancreatic, serum, and other tissues from a mouse model of chronic pancreatitis−induced osteoporosis (CP−OP), with the aim to elucidate the metabolism−related pathogenic mechanisms of CP−OP. Results: We identified over 405 metabolites and 445 lipids, and our findings revealed that several metabolites involving the tricarboxylic acid (TCA) cycle, as well as triacylglycerols and diacylglycerols with higher saturation, were significantly increased in the CP−OP model. In contrast, triglycerides with higher unsaturation were decreased. Differential pathways were enriched in n−3 long−chain polyunsaturated fatty acid metabolism in both pancreatic and bone tissues, and these pathways exhibited positive correlations with bone−related parameters. Furthermore, the modulation of these polyunsaturated fatty acids by Qingyi granules demonstrated significant therapeutic effects on CP−OP, as validated in mouse models. Conclusions: Through the metabolomics approach, we uncovered that disorders in polyunsaturated fatty acids play a critical role in the pathogenesis of CP−OP. This study not only enhances our understanding of the pathogenesis of CP−OP but also highlights the therapeutic potential of targeting polyunsaturated fatty acids as a future intervention strategy for osteoporosis treatment.